Rh(I)/NHC-Catalyzed Site- and Enantioselective Functionalization of C(sp3)–H Bonds Toward Chiral Triarylmethanes - Kim, Ju Hyun; Greßies, Steffen; Boultadakis-Arapinis, Mélissa; Daniliuc, Constantin; Glorius, Frank (ACS catalysis, 2016)
The first Rh(I)-catalyzed asymmetric approach for the intermolecular functionalization of C(sp3)–H bonds is reported. For the first time, unsymmetrical N-heterocyclic carbenes (NHCs) were used for asymmetric catalysis that is capable of achieving not only high site-selectivity but also enantioselectivity. The Rh(I)/NHC* catalytic systems were applied to asymmetric direct C(sp3)–H arylation, which provides a synthetic route toward enantioenriched triarylmethanes.